* Cybersecurity Awareness For High School Students At SMA Panca Budi Medan - Wirda Fitriani; Akhyar Lubis; Nova Mayasari (CV. Generasi Insan Rafflesia, 2026)
The rapid development of information technology has encouraged students to be more active in using digital devices and the internet for learning activities and daily communication. However, the use of these technological devices is not accompanied by adequate awareness regarding cybersecurity. This makes students vulnerable subjects to various digital threats such as phishing, data theft, account misuse, malware, and cyberbullying. This education aims to provide students at SMA Panca Budi with an understanding of the importance of cybersecurity and how to protect personal data. Awareness of personal data protection will provide security and protection for personal data, which is now increasingly stored digitally. As teenagers with high curiosity, it is important to provide education and practice in digital security by implementing stronger password creation, enabling two-factor authentication, recognizing indications of phishing attacks, and avoiding the prevalence of cyberbullying. It is hoped that this will increase students' cyber awareness in supporting a digital security culture within the school environment.